Home and away : contextual theology and local practice - Burns, Stephen, 1970-; Pearson, Clive (Eugene, Oregon : Pickwick Publications, 2013)
"Home and Away is a cluster of exercises in contextual theology, in different but related modes."--Preface.
Home and away, faith an identity in diaspora / Clive Pearson -- Postal-code 2016/2017, Redfern/Waterloo in South Sydney / Dorothy McCrae-McMahon -- Postal-code 3000, imaging sacred space / Simon Holt -- Cross of flowers, echoes of times past or a signpost toward a future? / Matthew Wilson -- For Christ's sake! post-coding Christ-talk / Michael N. Jagessar -- From seclusion to inclusion, envisioning God's kingdom for the mentally ill / Mary Pearson -- Wandering / Stephen Burns -- Displacing theology, God-talk in an "Age of Migration" / Susanna Snyder -- Homemaking in the diaspora, from displaced guest to responsible host / Seforosa Carroll -- Crossing postal codes in early modern Japan, the stories of Tamura Naomi and Osaka Motokichiro / Thomas Hastings.
Includes bibliographical references.
Description based on print version record.
Keywords: Pastoral care; Christianity -- Australia; Christianity and culture -- Australia; Christianity; Christianity and culture; Pastoral care; Australia; RELIGION / Christian Ministry / Pastoral Resources; Electronic books